(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
During her last semester prior to retirement, a university professor of teacher education supervised 15 interns enrolled in a preparation program and college department different from the professor’s usual program and department due to changes in the college’s preparation program student enrollment and faculty availability. The ever-changing, extraordinary circumstances experienced by the interns and supervisor during the 2020 spring semester illuminate the vital roles of readiness to teach, receptiveness to feedback, and responsiveness to expectations (Author & Merritt, 2018). Established on authentic expressions and exchanges of trust, efficacy, agency, and cultural humility (TEACH), their shared journeys yielded exceptional consequences for both the interns and the supervisor guided and supported by the supervisor’s expertise as teacher educator, co-constructivist, and instructional coach.